IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR DI TEPI JALAN UMUM DI KABUPATEN WONOSOBO - Jauza Sahda Shofiyana; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The parking fee policy on public roads is one of the local government's instruments to increase Local Own-Source Revenue (PAD) while maintaining order in the use of public space. However, in Wonosobo Regency, the realization of parking fee revenue has not been able to reach the target set by the local government. In 2024, the realization of parking fee revenue only reached around 53.38% of the target. This condition indicates a gap between the retribution revenue target and the collection practices in the field, which are characterized by parking fees that are not in accordance with the provisions, inconsistent use of parking tickets, and suboptimal parking supervision. This study aims to analyze the implementation of roadside parking retribution policy in Wonosobo Regency and identify the supporting and inhibiting factors in its implementation. The research used a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observations, and documentation. The analysis of policy implementation used the concept of policy success according to Riant Nugroho, while the factors influencing policy implementation were analyzed using the theory of Van Meter and Van Horn. The results of the study indicate that the implementation of the roadside parking fee policy in Wonosobo Regency has not been optimal. This is evident in the failure to achieve the parking fee revenue target, collection practices that are still influenced by old habits, inconsistent use of parking tickets, and low compliance with parking fees among parking attendants. Factors supporting policy implementation include the existence of regional regulations and the commitment of the local government, while inhibiting factors include limited parking supervision personnel, inconsistent use of parking tickets, and irregular coordination between agencies.